O impacto do livro didático da educação de jovens e adultos na percepção de alunos e de professores - Santos, Sonaly Sobral (2025)
This research analyzes the impact of Textbooks (LD) on Youth and Adult Education (EJA), considering the perceptions of teachers and students, and aimed to understand the possible contributions and limitations of the use of Textbooks for teaching and learning. The research adopted a qualitative approach, based on a case study, and used content analysis to interpret the data collected. The study was carried out in a reference school for this modality, with the application of questionnaires to teachers and students, in addition to the documentary analysis of the legislation that guarantees the right to education and also of the National Program for Material and Textbooks (PNLD EJA). The data analysis was structured in emerging categories, seeking to understand the relationships between Textbooks and the specific challenges of EJA. The results indicated that, although Textbooks are considered an important resource, the school did not adopt textbooks, and this absence influences the quality of teaching, making lesson planning difficult and overloading teachers in the search for materials appropriate to the specificity of EJA. For students, the lack of LD harms learning, reducing motivation and academic performance, a situation that highlights the urgency of resuming the PNLD EJA for High School.